(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
A new type of portland cеment has been obtained by using troctoliteharzburgite rocks of northeastern part of Sevan Lake, the strength of which is nearly 20% higher than ordinary portland cement. The obtained binder will give possibility to save more than 20–30% cement clinker and simultaneously will increase the strength of the cement stone.